Phenomenological Study: The Impact of Financial Technology on Financial Satisfaction (Case Study of Meatball and Chicken Noodle Traders in Jagakarsa District) - Yatimin Yatimin; Suhendar Sulaiman; Adi Musharianto; Yanti Budiasih (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to examine the influence of financial technology (Fintech) on the financial satisfaction of micro business actors, especially meatball and chicken noodle traders in Jagakarsa District, South Jakarta. Using a phenomenological approach combined with the Analytic Hierarchy Process (AHP) method, this study explores how Fintech features such as transaction security, ease of access, ease of use, speed, and transaction costs affect user satisfaction. Data was collected through in-depth interviews with 15 selected vendors and the administration of a paired comparison questionnaire. The results show that transaction security is the most dominant factor influencing financial satisfaction, followed by ease of access and ease of use. Speed and cost are considered less important. Among the Fintech alternatives evaluated, e-wallets (e.g., GoPay, OVO, DANA) are rated as the most effective tools in increasing satisfaction, slightly outperforming mobile banking. QRIS has a moderate impact, while digital lending received the lowest rating due to concerns over complexity and risk. These findings show that Fintech solutions aimed at micro-entrepreneurs must prioritize simplicity, accessibility, and most importantly, trust. The study contributes to the growing body of literature on digital financial inclusion, which offers practical implications for Fintech developers, policymakers, and financial institutions seeking to support informal sector businesses through inclusive, user-centric digital innovation.